Pelatihan Penataan Produk Secara Visual untuk Meningkatkan Minat Beli Konsumen Toko Al-Amin Weleri - Isnawati, Setya Indah; Ali, Ahmad; Jayanti, Fitri Dwi; Prihantini, Isra (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Visually appealing product arrangement plays a crucial role in influencing consumer purchase interest. Visual merchandising is a marketing strategy that focuses on arranging products in stores aesthetically and strategically to attract customer attention, create an enjoyable shopping experience, and encourage impulsive buying. This study aims to enhance the attractiveness of Al-Amin Weleri store through training on visual product arrangement. The training involves demonstrations, hands-on practice, and evaluations to help store managers understand the fundamental principles of visual merchandising, such as product grouping, color usage, lighting, and effective layout arrangement. The results of the activity indicate an improvement in the managers’ understanding and skills in arranging products, which positively impacts consumer purchase interest. By implementing better visual arrangements, Al-Amin Weleri store is expected to enhance its competitiveness and attract more customers.